ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM PERALIHAN SERTIFIKAT HAK MILIK BERDASARKAN PUTUSAN NOMOR 29/Pdt.G/2024/PN.Ptk - NIM. A1012211065, WANDA FINDRA MICHELLINA (Jurnal Fatwa Hukum, 2025)
Abstract The transfer of land rights through sale and purchase without an official deed made before a Land Deed Official (PPAT) still frequently occurs in Indonesia, including in Pontianak City, and often leads to legal problems. One concrete case is Decision Number 29/PDT.G/2024/PN.PTK concerning an informal land sale between Mardiyah Marsuni and Suhardi, which was later used as the basis for an application to change the name on the land certificate at the Land Office. This study aims to analyze the legal considerations of the judge in determining the validity of a sale and purchase conducted without an authentic deed, as well as to examine its legal consequences for the parties involved. This research employs a normative legal method with a descriptive-analytical approach, using literature study of primary, secondary, and tertiary legal materials, and combines a statute approach with a case approach. The results show that the transfer of land rights is valid only if carried out through a PPAT deed and registered with the Land Office in accordance with Article 37 of Government Regulation Number 24 of 1997. In this case, the plaintiff was proven to have a clear legal standing and acted in good faith, while the defendant failed to follow lawful procedures and was absent during the trial. The judge emphasized legal certainty, protection of the rightful owner, and the principle of justice. The court ultimately granted the lawsuit, declared the transfer of rights valid, and ordered the defendant to hand over the land to the plaintiff as the lawful owner. Keywords: Transfer, Certificate, Decision, Consideration Abstrak Peralihan hak atas tanah melalui mekanisme jual beli tanpa akta Pejabat Pembuat Akta Tanah (PPAT) masih sering terjadi di Indonesia, termasuk di Kota Pontianak, dan kerap menimbulkan permasalahan hukum. Salah satu kasus konkret adalah Putusan Nomor 29/PDT.G/2024/PN.PTK terkait jual beli bawah tangan antara Mardiyah Marsuni dan Suhardi, yang kemudian menjadi dasar permohonan balik nama sertifikat di Kantor Pertanahan. Penelitian ini bertujuan menganalisis pertimbangan hukum hakim dalam menetapkan keabsahan jual beli tanpa akta otentik serta mengkaji akibat hukumnya bagi para pihak. Penelitian menggunakan metode hukum normatif dengan sifat deskriptif-analitis melalui studi kepustakaan terhadap bahan hukum primer, sekunder, dan tersier, serta mengombinasikan pendekatan perundang-undangan (statute approach) dan pendekatan kasus (case approach). Hasil penelitian menunjukkan bahwa peralihan hak atas tanah hanya sah apabila dilakukan melalui akta PPAT dan didaftarkan ke Kantor Pertanahan sesuai Pasal 37 PP Nomor 24 Tahun 1997. Dalam perkara ini, penggugat terbukti memiliki kedudukan hukum yang jelas serta bertindak dengan itikad baik, sedangkan tergugat tidak mengikuti prosedur sah dan absen dalam persidangan. Hakim menekankan kepastian hukum, perlindungan hak pemilik, dan asas keadilan. Putusan akhirnya mengabulkan gugatan, menyatakan peralihan hak sah, serta mewajibkan tergugat menyerahkan tanah kepada penggugat. Kata Kunci: peralihan, sertifikat, putusan, pertimbangan hukum